A preliminary factor analytic investigation into the first-order factor structure of the fifteen factor questionnaire plus on a sample of black South African managers - Moyo, Seretse (Stellenbosch : Stellenbosch University, 2009)
Thesis (MComm (Industrial Psychology))--Stellenbosch University, 2009.